2018
DOI: 10.1097/ccm.0000000000003077
|View full text |Cite
|
Sign up to set email alerts
|

The Period 2 Enhancer Nobiletin as Novel Therapy in Murine Models of Circadian Disruption Resembling Delirium*

Abstract: These experiments identify a novel role for PER2 during a midazolam- or constant light-induced delirium-like state, highlight the importance of hippocampal PER2 expression for cognitive function, and suggest the PER2 enhancer nobiletin as potential therapy in delirium-like conditions associated with circadian disruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 51 publications
(63 reference statements)
1
34
0
Order By: Relevance
“…While midazolam is the benzodiazepine most frequently used for procedural sedation, recent clinical data suggest that midazolam is associated with severe clinical complications. As such midazolam has been associated with the occurrence of delirium and is therefore not recommended anymore as first line sedative on critical care units [2932]. Moreover, a recent study found that continuous infusion of benzodiazepines is linked to an increased likelihood of death among patients who receive mechanical ventilation, when compared to the sedative propofol [11].…”
Section: Discussionmentioning
confidence: 99%
“…While midazolam is the benzodiazepine most frequently used for procedural sedation, recent clinical data suggest that midazolam is associated with severe clinical complications. As such midazolam has been associated with the occurrence of delirium and is therefore not recommended anymore as first line sedative on critical care units [2932]. Moreover, a recent study found that continuous infusion of benzodiazepines is linked to an increased likelihood of death among patients who receive mechanical ventilation, when compared to the sedative propofol [11].…”
Section: Discussionmentioning
confidence: 99%
“…pharmacologic approach to induce Per2 has been previously demonstrated to treat metabolic dysfunction (23). As a therapeutic strategy, inducing Per2 circadian rhythms with nobiletin, a nontoxic flavonoid, has been identified as advantageous in treating circadian dysfunctional diseases such as obesity and oxidative stress in mice (23,40). Nobiletin is a flavonoid derived from a citrus plant, which suggests that potent antioxidative effects can function to reduce reactive oxygen species, which contribute to disease progression (23,41).…”
Section: Discussionmentioning
confidence: 99%
“…For example, nocturnal light exposure decreases the secretion of melatonin, a hormone secreted by the pineal gland in response to darkness, which can ultimately result in sleep disruption [2]; the disruption of the circadian rhythm seen in patients with severe sepsis ( n = 7) was reflected in the first 48 h of ICU admission by disordered diurnal variation of urinary 6-SMT excretion [10]. In animal models, circadian rhythm disruption due to constant light exposure led to reduced expression of Per-2 in the SCN and subsequent behavioral symptoms of delirium (i.e., executive dysfunction and memory impairment) [11]. Clinical symptoms were reversed with nobiletin, a known enhancer of Per-2 function [11].…”
Section: Mechanisms and Physiological Consequences Of Sleep Disturbanmentioning
confidence: 99%
“…In animal models, circadian rhythm disruption due to constant light exposure led to reduced expression of Per-2 in the SCN and subsequent behavioral symptoms of delirium (i.e., executive dysfunction and memory impairment) [11]. Clinical symptoms were reversed with nobiletin, a known enhancer of Per-2 function [11]. Findings of diurnal disruption have been reported in traumatic brain injury (TBI), trauma and medical patient populations [12]; any association between diurnal disruption and resultant outcome (e.g., sedative use, incidence delirium or length of stay) in these patient populations has yet to be demonstrated.…”
Section: Mechanisms and Physiological Consequences Of Sleep Disturbanmentioning
confidence: 99%